Effect of Training Modules on Hip Fracture Surgical Skills Simulation Performance: Early Validation of the AAOS/OTA Simulator. (20th November 2019) - Weber, Annie; Domes, Christopher; Christian, Matthew; Coale, Max; Griffith, Cullen; O'Hara, Nathan N.; Henn, R. Frank; O'Toole, Robert V.; Sciadini, Marcus F.
Abstract : Background: A preliminary validation study on a computer-based force-feedback simulation platform demonstrated the ability of the simulator to distinguish between novice and experienced users during a simulated hip-pinning procedure. The purpose of the present study was to further investigate whether the simulator and associated training modules are effective for improving user performance during simulated percutaneous hip-pinning procedures. Methods: With institutional review board approval, 24 medical students at our institution were randomized to "Trained" and "Untrained" groups. After a basic introduction, the Untrained group placed 3 guidewires in a valgus-impacted femoral neck fracture with use of the simulator. The Trained group completed 9 simulator-based training modules before performing the same task. Measured outcomes included an overall performance score and the distance from the pin to various ideals on the femoral neck, femoral head articular surface, and lateral cortex. Performance parameters were compared between groups with the Mann-Whitney U test. Results: The Trained group achieved a significantly higher overall score (median, 29) compared with the Untrained group (median, 6) (p < 0.01), outperformed the Untrained group in 4 specific performance metrics, and trended toward improvement over the Untrained group in 4 pin placement measures (p < 0.2). Conclusions: Completion of novel training modules for percutaneous hip pinning on this fluoroscopic surgery simulator improves skill performance on simulator-based objective measurements and a simulated orthopaedic procedure compared with non-simulator-trained surgically inexperienced users. Improvement in the overall score and on 4 of 13 specific performance parameters implies that the training modules more effectively teach only certain motor and 3-dimensional spatial skills. Clinical Relevance: A valid platform such as the one described here has the potential to improve surgical education in orthopaedic trauma.